2005
DOI: 10.1021/ja054508j
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Field Switched Ordered Arrays of Dinuclear Mixed-Valence Complexes on the Distance between the Redox Centers and the Size of the Counterions

Abstract: trans-[(H(2)NCH(2)CH(2)C triple bond N)(dppe)(2)Ru(C triple bond C)(6)Ru(dppe)(2)(N triple bond CCH(2)CH(2)NH(2))][PF(6)](2), 2[PF(6)](2), a derivative of trans-[Cl(dppe)(2)Ru(C triple bond C)(6)Ru(dppe)(2)Cl] functionalized for binding to a silicon substrate, has been prepared and characterized spectroscopically, electrochemically, and with a solid state, single-crystal structure determination. Covalent binding via reaction of one amine group to a boron-doped, smooth Si-Cl substrate is verified by XPS measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
98
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 29 publications
2
98
0
Order By: Relevance
“…78 This Quantum Cellular Automata (QCA) paradigm transmits binary information utilizing electric field coupled cells rather than current flow. A prototype of a biased two-dot molecular QCA was realised with the ruthenium complex [(H 2 NCH 2 CH 2 C N)-(dppe) 2 Ru(C C) 6 Ru(dppe) 2 (30), functionalized for binding to a silicon substrate.…”
mentioning
confidence: 99%
“…78 This Quantum Cellular Automata (QCA) paradigm transmits binary information utilizing electric field coupled cells rather than current flow. A prototype of a biased two-dot molecular QCA was realised with the ruthenium complex [(H 2 NCH 2 CH 2 C N)-(dppe) 2 Ru(C C) 6 Ru(dppe) 2 (30), functionalized for binding to a silicon substrate.…”
mentioning
confidence: 99%
“…[7] The modification of conducting surfaces at the molecular level with redoxactive ''building blocks'' constitutes a powerful approach to the fabrication of such materials, particularly when the goal is integrated systems devoted to information storage or transfer. [8][9][10] For such applications, technologically relevant semiconducting surfaces, such as doped silicon, constitute particularly attractive substrates; indeed, silicon surfaces covalently derivatized with reversible redox-center-terminated organic monolayers [1,2,8,[11][12][13][14] have recently been prepared and examined to determine if molecular memories could result from such hybrid junctions. In parallel with these seminal studies, there have been relevant developments with redoxactive carbon-rich group 8 organometallics.…”
mentioning
confidence: 99%
“…In parallel with these seminal studies, there have been relevant developments with redoxactive carbon-rich group 8 organometallics. These compounds are ideal candidates for reversible charge storage at the molecular level, [15][16][17][18][19][20] and recently Fehlner, Blum, and Rigaut have independently established that both homo-and heteropolynuclear representatives of this class of molecules can be anchored on conducting silicon [9,10] or gold [21,22] interfaces.The studies of bundles/monolayers on gold have revealed far better conduction through these organometallic substrates than through purely organic analogues of similar length, [21,22] while the studies on silicon surfaces have shown that a given redox state of the immobilized molecules can be generated by application of a suitably chosen electrical potential to this hybrid junction. [9,10] In complementary studies in the field of optics, [23] we have recently demonstrated that electrochemical generation of the various redox congeners of the dinuclear Fe(II)/Ru(II) complex 1 (Scheme 1) [24] provides a means to modulate the linear and nonlinear optical properties of a solution of these compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ESDs not reported in [117,120] f The structure of [5]Ph was reported without values for bond lengths and angles, see [118]; Bond lengths and angles from Januszewski et al The bond angles of the [n]cumulenes approach 180 as expected for linear molecules, and deviations are negligible for all derivatives (<2 ), except for [3]Ph which shows angles of 176.3 (2) . While only a small number of structures are available, the linearity of the [n]cumulenes stands in stark contrast to that observed for polyynes (vide infra), where bending of the sp-carbon polyyne chain is often observed, even in short derivatives [45,76,78,85,121].…”
Section: Cumulenesmentioning
confidence: 97%